Recent advances in theranostic agents based on natural products for photodynamic and sonodynamic therapy. Issue 3 (25th July 2020) - Wu, Jiasheng; Sha, Jie; Zhang, Chuangli; Liu, Weimin; Zheng, Xiuli; Wang, Pengfei
Abstract: The integration of diagnosis and therapy based on natural products has been receiving considerable attention in recent years because nature can contribute many fantastic functional molecules with good biocompatibility and low toxicity. Diagnostic and therapeutic agents combined with the technique of photodynamic therapy (PDT) and sonodynamic therapy (SDT) have been extensively developed thanks to the advantages of PDT and SDT, such as good selectivity, low toxicity, and noninvasive treatment for cancers and other diseases compared with traditional treatments. In this review, we summarize the recent advances in theranostic agents for natural products categorized as porphyrins, perylenequinone, curcumin, and others. Some representative examples of disease diagnosis in fluorescence/photoacoustic imaging and disease treatment in PDT/SDT were introduced. Potential limitations and future perspectives of these natural products for theranostic agents were also discussed. Abstract : In this review, the authors summarize recent advances in theranostic agents for natural products categorized as porphyrins, perylenequinone, curcumin, and others. Some representative examples of disease diagnosis in fluorescence/photoacoustic imaging and disease treatment in PDT/SDT are introduced. Potential limitations and future perspectives of these natural products for theranostic agents are also discussed.